Free-sodium salts mixture and AlgySalt® use as NaCl substitutes in fresh and cooked meat products intended for the hypertensive population. (November 2017) - Triki, M.; Khemakhem, I.; Trigui, I.; Ben Salah, R.; Jaballi, S.; Ruiz-Capillas, C.; Ayadi, M.A.; Attia, H.; Besbes, S.
Abstract: This work aims at reducing the use of added NaCl in processed meat products because of its negative effects on hypertensive population by replacing it by sodium-free salts mixture (SM: KCl, MgCl2 and CaCl2 ) in fresh and cooked sausages. The technological, sensory, and microbiological effects of SM were compared with a commercial replacer based on seaweed extracts (AlgySalt®). A total substitution of NaCl with the latter and a partial one with SM (80% and 50%) were studied in cooked sausages and a total NaCl substitution with both substitutes was performed in fresh sausages. As a result, hardness increased in AlgySalt® reformulated samples, while it decreased when 80% SM were used. Whereas, AlgySalt® induced less cooking loses than SM. To some extent, microbiological counts showed a similarity between reformulated and control samples for both sausage types, whereas reformulated products containing SM revealed better sensory properties for both meat products. Therefore, using SM as NaCl replacer is adequate for processed meat products. Highlights: NaCl substitution effect on sausages physicochemical and microbial properties Instrumental and sensory profiles of reformulated sodium-reduced meat products Comparison between free-sodium salt mixture and AlgySalt® as NaCl substitutes Reformulation strategy optimization for reduced-sodium meat sausages production. Reduced-sodium meat products destined for hypertensive population